Legal Risks and Preventive Countermeasures of the “Shared Labor” Model - Jianming Zhong (Law and Economy, 2023)
Shared Labor is on the rise in China since the epidemic. Due to the lack of uniform applicable standards and legal norms, under the principle of “the original labor relationship remains unchanged”, flexible innovation is carried out in combination with practical needs, and the following characteristics are presented in the short-term exploration: complicated and diversified modes of labor employment; dual subjects of labor employment; the coexistence of traditional typical and atypical labor; and sharing of platforms. The trend of on-line labor employment is prominent. Shared labor is a new type of employment pattern spawned by the new Crown Pneumonia epidemic, which faces the short board of unclear legal application, leading to legal risks and litigation hazards in practice. In practice, there are two basic legal risks, one is the risk of identifying the type of employment; the other is the risk of identifying the legal relationship. This also extends to secondary legal risks, involving work injury insurance treatment, change of labor relationship, employee return and labor contract termination, employment discrimination, administrative liability and many other issues. Therefore, this paper summarizes the three major modes of labor sharing, i.e., B2B mode, BPC mode, and B2C mode, and proposes preventive countermeasures after analyzing their legal risks.